Finance-based Scheduling for Cash-flow Management of Maintenance Portfolios: Multi-objective Optimization Approach - Fares, Ali; Elazouni, Ashraf; Al-Alawi, Mubarak (Decision Making: Applications in Management and Engineering, 2024)
Bridge agencies are often challenged to develop maintenance programs under given budgets. Numerous studies developed budget-allocation models for maintenance programs during defined planning horizons of multiple fiscal years while totally ignoring the crucial aspect of cash flow. The payment schedules (both timing and amount) for contractors might indicate agencies’ cash needs that exceed the available budgets during certain fiscal years, which create cash flow problems. While numerous finance-based scheduling (FBS) models were developed to manage cash flow for contractors, this function was totally overlooked for portfolio owners. Thus, this research reintroduces the FBS from the perspective of portfolio owners. A FBS model is developed to schedule the activities of the portfolio projects, utilize the schedules to define the payment schedules of projects’ contractors, calculate the agencies’ cash needs during the fiscal years, and utilize the multi-objective optimization algorithms of NSGA-II, SPEA-II, and MOPSO to optimize the projects’ schedules to achieve a balance between the cash needs during the fiscal years and the available budgets. The anticipated extensions in projects’ completion represent the conflicting objectives. Finally, the optimized schedules make the contractors’ payment schedules affordable by the agencies’ budgets, which help to complete projects successfully and achieve the programs’ strategic goals.